Hubungan Titer Widal Dengan Jumlah dan Indeks Trombosit Penderita Demam Tifoid di Puskesmas Wilayah Lombok Barat - Widary, Baiq Larasati; Danuyanti, I Gusti Ayu Nyoman; Zaetun, Siti (Faculty of Medicine, Universitas Andalas, 2021)
The diagnosis of typhoid fever can be made by hematological examination and the Widal method. Hematologic change that often occurs in typhoid fever is thrombocytopenia. Platelet function can be observed by examining the platelet index, namely the Mean Platelet Volume (MPV), and Platelet Distribution Width (PDW). The titer on the serological examination of the Widal test is a significant diagnostic for infections caused by the bacterium Salmonella typhi. Objectives: To determine the relationship between the Widal titer and the number and index of platelets in patients with typhoid fever at the West Lombok Health Center. Methods: The research methodology used is an analytic observational method with a cross-sectional approach. This study was conducted from February 2021 to April 2021. The population in this study was all patients who underwent laboratory examinations diagnosed as positive for typhoid fever in the Gunungsari Health Center, West Lombok Regency, with a sample of 24 respondents. Data analysis using Spearman correlation. Results: Statistical test results obtained Pâ‰¥0.05, namely the titer value against platelets p=0.429, the titer against the MPV platelet index p=1,000, PDW p=0.291. Conclusion: there is no relationship between widal titer to the number of platelets and the platelet index in patients with typhoid fever.Keywords: Â typhoid fever, platelets, platelet Â index, widal titer